2023
DOI: 10.1002/ecs2.4444
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic use of UAV surveys, satellite tracking data, and mark‐recapture to estimate abundance of elusive species

Abstract: Estimating population abundance is central to many ecological studies and important in conservation planning. Yet the elusive nature of many species makes estimating their abundance challenging. Abundance estimates of sea turtles, marine birds, and seals are usually made when breeding adults are ashore, while life stages spent at sea, including as juveniles, are often poorly sampled. We used a combination of high‐resolution satellite tracking (Fastloc‐GPS), uncrewed aerial vehicle (UAV) surveys, and capture‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Flights at Turtle Cove on Diego Garcia were excluded from this analysis because they were targeted at a known immature turtle aggregation (Stokes et al., 2023) area and could not therefore be expected to give a representative picture of turtle distribution in the area. Exploratory analysis of the remaining data revealed that turtle and teleost detections were too spatially aggregated to support robust statistical inference, however, elasmobranch observations were sufficiently dispersed.…”
Section: Methodsmentioning
confidence: 99%
“…Flights at Turtle Cove on Diego Garcia were excluded from this analysis because they were targeted at a known immature turtle aggregation (Stokes et al., 2023) area and could not therefore be expected to give a representative picture of turtle distribution in the area. Exploratory analysis of the remaining data revealed that turtle and teleost detections were too spatially aggregated to support robust statistical inference, however, elasmobranch observations were sufficiently dispersed.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, drones can access and survey challenging marine areas that are typically inaccessible or hazardous for humans [96,97]. This enables data collection from remote or neglected locations, providing a comprehensive understanding of species populations, habitat conditions, and environmental changes.…”
Section: Coastal Zone Ecological Monitoringmentioning
confidence: 99%
“…On the other hand, mortality records of reproductive females at nesting beaches also inform about in‐land threats that frequently cause the deaths of individuals in the breeding population. Available technology has made it feasible to expand this on‐site knowledge using tools such as satellite telemetry, vessel‐based surveys, bycatch quantification and drone imagery to maximize the information regarding the injury or death causes for those stranded or rescued individuals (Raoult et al, 2020; Schofield et al, 2019; Stokes et al, 2022). The combination of several of these data sources proved to be effective when integrated with ocean circulation models to evaluate the spatial distribution of male sea turtles (Cuevas et al, 2020; Nero et al, 2013) and the distribution of offspring during the ‘lost years’, which typically occur in oceanic zones (Putman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%